2022
DOI: 10.1093/cvr/cvac102
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of the Hippo effector YAP by the methyltransferase SETD7 drives myocardial ischaemic injury: a translational study

Abstract: Aims Methylation of non-histone proteins is emerging as a central regulatory mechanism in health and disease. The methyltransferase SETD7 has shown to methylate and alter the function of a variety of proteins in vitro, however its function in the heart is poorly understood. The present study investigates the role of SETD7 in myocardial ischemic injury. Methods and Results Experiments were performed in neonatal rat ventricular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Within hours, a regulated inflammatory response consisting mainly of neutrophils and monocyte/macrophages is initiated in the myocardium to remove dead cells and matrix debris 38 . In addition, apoptotic cardiomyocytes induced by myocardial inflammatory response are present in the surviving portion of the wall adjacent to the ischemic area 39 . The present study has shown that WWP1 governs an inflammatory program in cardiomyocytes to increase myocardial inflammation and apoptosis after MI.…”
Section: Discussionmentioning
confidence: 99%
“…Within hours, a regulated inflammatory response consisting mainly of neutrophils and monocyte/macrophages is initiated in the myocardium to remove dead cells and matrix debris 38 . In addition, apoptotic cardiomyocytes induced by myocardial inflammatory response are present in the surviving portion of the wall adjacent to the ischemic area 39 . The present study has shown that WWP1 governs an inflammatory program in cardiomyocytes to increase myocardial inflammation and apoptosis after MI.…”
Section: Discussionmentioning
confidence: 99%
“…Under physiological conditions, a small proportion of ROS generated is rapidly scavenged by internal antioxidative systems 32 . However, these systems are severely disrupted during I/R, which contributes to excessive ROS production and leads to the initial myocardial reperfusion injury 33 . Thus, enhancing the activity of antioxidative enzymes may be a good strategy to decrease the oxidative stress‐elicited reperfusion damage 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to SET1A, the methylation of YAP can also be induced by suppressor of variegation 3‐9‐enhancer of zeste‐trithorax domain containing lysin E methyltransferase 7 (SETD7). SETD7 can methylate the YAP at lysine 494 to inhibit the transfer of YAP to the nucleus, thus reducing the transcription of antioxidant genes manganese superoxide dismutase (MnSOD) and catalase (CAT) ultimately to protect the heart 131 . Spectrin beta, nonerythrocytic 1 (SPTBN1) can promote the expression of SETD7 to enhance YAP methylation, and ultimately plays a role in cell autophagy 132 …”
Section: The Regulation Of Yap/tazmentioning
confidence: 99%
“…SETD7 can methylate the YAP at lysine 494 to inhibit the transfer of YAP to the nucleus, thus reducing the transcription of antioxidant genes manganese superoxide dismutase (MnSOD) and catalase (CAT) ultimately to protect the heart. 131 Spectrin beta, nonerythrocytic 1 (SPTBN1) can promote the expression of SETD7 to enhance YAP methylation, and ultimately plays a role in cell autophagy. 132 The O-GlcNAcylation of YAP has been mentioned above.…”
Section: 8mentioning
confidence: 99%